MALIGNANT OVARIAN TUMORS DIAGNOSTICS DIFFICULTIES - S. O. Nikoghosyan; A. Z. Zagashtokov; N. E. Levchenko; M. M. Thakokhov (ABV-press, 2018)
Despite the undeniable successes of modern medicine, the problems of oncology and, in particular, oncogynecology are still unresolved. Thus, a 5-year overall survival rate for stage I ovarian cancer is 89 %, for stage IV - 17 %. Given that complaints in patients with ovarian cancer appear only after the tumor has passed beyond the organ, the most important and key factor in successful treatment is the correct diagnosis of ovarian neoplasm. Observance of the correct algorithm and correct surgery can significantly improve the results of treatment. The article will discuss the difficulties of diagnosing ovarian cancer.